In vivo sensitivity test of Chloroquin on Plasmodium falciparum : A Study at Pituruh Sub District, Purworejo - Rina Handayani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Until now Malaria remains a major health problem in Indonesia. Purworejo one of the regencies in Central Java, is a malaria endemic area and the prevalence remains the same even though some efforts to eliminate the disease have been done. This study was aimed to investigate the susceptibility of P. falciparum to chloroquine, extended in vivo test was used. Subject were enrolled using mass blood survey and mass fever survey. This study show that 45,6% P. falciparum was resistant to chloroquine, consisted of RI early recrudescence (16.22%), RI delayed recrudescence (8.11%), RII (16.22%), RIII (5.41%).Key word: invivo test, P. falciparum, chloroquine